CRISPR-mediated genome editing in poplar issued by efficient transformation - Movahedi, Ali; Wei, Hui; Kadkhodaei, Saeid; Sun, Weibo; Zhuge, Qiang; Yang, Liming; Xu, Chen (Frontiers in Plant Science, 2023)
Background CRISPR has been increasingly used for plant genetic improvements because of its high efficiency and precision. Recently, the authors have reported the possibility of homology-directed repair (HDR) using CRISPR/Cas9 through woody plants such as poplar. HDR often replaces nucleotides with one donor DNA template (DDT), including homologous sequences. Methods CRISPR–Cas9 was recruited, and three variables, Agrobacteria inoculator concentration, pDDT/pgRNA ratio, and homologous arm length, were designed to integrate nptII and 2XCamV 35S into the MKK2 promoter zone. Results Here, we showed that recovered poplars on kanamycin-supplemented media exhibited enhanced expression of MKK2 affected by the precise integration of 2XcamV 35S and nptII, improving biochemical and phenotypic properties. Our findings confirmed that Agrobacterium inoculator OD600 = 2.5, increased DDT numbers during cell division to 4:1 pDDT/pgRNA, and optimized homologous arms 700 bp caused efficient HDR and increased MKK2 expression. Conclusion Efficient transformations resulted from optimized variables, directly affecting the HDR efficiency through woody plants such as poplar.